Evaluation of an aquatic liverwort and terrestrial moss as biomonitors of heavy metals associated with particulate matter - Clara Gómez-Ensastegui; Pedro Avila-Pérez; José Luis García-Rivas; Carlos Eduardo Barrera-Díaz; Huemantzin Balan Ortiz-Oliveros; Sonia Martínez-Gallegos (Scientific Reports)
Abstract In this study, the capacity of the aquatic liverwort Ricciocarpus natans L. and the terrestrial moss Entodon serrulatus Mitt. as biomonitors of heavy metals associated with particulate matter from a highly polluted urban area was evaluated, and concentrations in moss tissues were correlated with concentrations of PM10 and PM2.5 present in the atmosphere. The two species were exposed by the moss bag technique to the pollution of the Toluca Valley Metropolitan Area (TVMA) for two periods of 6 months, using the sites of the Automatic Atmospheric Monitoring Network of the Government of the State of Mexico, and were subsequently analyzed using elemental and structural characterization techniques. The results show that mainly the functional groups -OH and -NH, N-H and C-O on the surface of the liverwort and moss participate in the adsorption of heavy elements. The average enrichment factors of Cd and Pb show to be highly enriched (> 10) in the study area while chromium is not enriched (< 2). The statistical results indicate a temporary variation in the concentration of metals and particles in the atmosphere, where there is a lower concentration of these pollutants in the rainy and dry-cold season and a higher concentration in the dry-hot season and a possible association of Cr and Cd with PM10 and PM2.5. In addition, except for Cr, both species accumulate the metals associated with airborne particulate matter at equivalent levels. There is strong association between PM2.5 and PM10 particles and between the metals Cr-Pb-Fe in R. natans and between PM2.5-PM10 and Fe and between Cd-Cr-Pb in E. serrulatus and these pollutants are mainly associated with sampling sites with the highest concentrations of metals in the TVMA. Although terrestrial moss showed slightly better characteristics than aquatic liverwort as a biomonitor of heavy metals associated with atmospheric particles, these differences were not statistically significant for all metals, so both species could be useful for heavy metal biomonitoring in highly polluted urban areas.